Psychological capital as a team phenomenon: Mediating the relationship between learning climate and outcomes at the individual and team levels. Issue 3 (3rd May 2016) - Heled, Efrat; Somech, Anit; Waters, Lea
Abstract : Psychological capital is a positive psychological state that influences employees' behaviors and attitudes. Research has only recently begun to examine the phenomenon as a shared psychological team state. The purpose of this research is to examine the mediating role of team psychological capital in the relationship between learning climate and outcomes at the individual and team levels. The findings, which were carried out among 82 school management teams, indicated a positive relationship between learning climate and the team's psychological capital, and between the team's psychological capital and the individual's job satisfaction and the team's organizational citizenship behavior (OCB). It was also found that team's psychological capital mediates the relationship between the team's learning climate and job satisfaction, and between learning mechanisms and the team's OCB. The findings might encourage research into psychological capital as a team phenomenon and encourage decision-makers to develop ways of reinforcing psychological capital among teams.